2023
DOI: 10.3390/cancers15153845
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics and Machine Learning in Brain Tumors and Their Habitat: A Systematic Review

Mehnaz Tabassum,
Abdulla Al Suman,
Eric Suero Molina
et al.

Abstract: Radiomics is a rapidly evolving field that involves extracting and analysing quantitative features from medical images, such as computed tomography or magnetic resonance images. Radiomics has shown promise in brain tumor diagnosis and patient-prognosis prediction by providing more detailed and objective information about tumors’ features than can be obtained from the visual inspection of the images alone. Radiomics data can be analyzed to determine their correlation with a tumor’s genetic status and grade, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
1
0
Order By: Relevance
“…In particular, glioblastoma, either on its own or combined with metastasis as a super-class of aggressive tumors, is the subject of many studies, with some others also including other frequent super-classes such as low-grade glioma or meningioma, while minority tumor types and grades are only considered in a limited number of studies. Importantly, and related to our previous comments concerning scarce data availability, most of the studies reported in [32] work with very small sample sizes, often not reaching the barrier of 100 cases. The challenge posed by data scarcity is compounded by the fact that most of the studies extract Radiomic features in the hundreds if not the thousands.…”
Section: Ml-based Analytical Pipelines and Their Use In Neuro-oncologymentioning
confidence: 78%
See 1 more Smart Citation
“…In particular, glioblastoma, either on its own or combined with metastasis as a super-class of aggressive tumors, is the subject of many studies, with some others also including other frequent super-classes such as low-grade glioma or meningioma, while minority tumor types and grades are only considered in a limited number of studies. Importantly, and related to our previous comments concerning scarce data availability, most of the studies reported in [32] work with very small sample sizes, often not reaching the barrier of 100 cases. The challenge posed by data scarcity is compounded by the fact that most of the studies extract Radiomic features in the hundreds if not the thousands.…”
Section: Ml-based Analytical Pipelines and Their Use In Neuro-oncologymentioning
confidence: 78%
“…The former may include first-order statistics, size and shape-based features, image intensity histogram descriptors, image textural information, etc. The use of this method for the pre-processing of brain tumor images prior to the use of ML has been recently and exhaustively reviewed in [32]. From that review, it is clear that the predominant problem under analysis is diagnosis, with only a limited number of studies addressing prognosis, survival, and progression.…”
Section: Ml-based Analytical Pipelines and Their Use In Neuro-oncologymentioning
confidence: 99%
“…Unsatisfactory diagnostic accuracy was also revealed according to these previous studies. What's more, research on the differential diagnosis of PCNSL from SBM based on radiomics is scarce [22,23].…”
Section: Discussionmentioning
confidence: 99%